Tranformasi Pantai Menjadi Destinasi Unggulan: Sinergi Pemerintah, Komunitas, dan UMKM di Desa Remen Tuban - Siswoyo; Ningtias, Nur Asri Fitri Rahmawati; Janah, Siti Miftaqul; Alsiva, Vahimatul; Nisa’, Kholifatun; Firdaus, Izzatul; Laela, Nurul; Nafiah, Sholihatin; Fawaid, Ahsana; SN, Izzah Qoimatul Isti'adah; Rizqi, M. Bicharur (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to identify the success factors, challenges, and forms of synergy between the Remen village government, the community within it and the UMKM in Remen village in developing Remen Beach as a leading tourist destination. This study uses a qualitative-descriptive method that describes the tourism potential of Remen's white sand beach. Qualitative research is research used to examine the condition of natural objects, where the researcher is the key instrument (Sugiono). The purpose of this qualitative research method is to gain a deep and comprehensive understanding of a phenomenon or problem through descriptive data collection, such as through in-depth interviews, direct observation, and document review. In the development of Remen White Sand Beach, social aspects must be prioritized, regardless of the type of activity or program undertaken. The involvement and interests of the local community are key elements that cannot be ignored. The success of Remen's tourism destination development depends heavily on strong social foundations, such as mutual cooperation, a sense of ownership, and active community participation in maintaining and sustainably managing the tourist area. Several govern tourism development, including safety, order, cleanliness, coolness, beauty, friendliness, and memories, are key elements. These principles serve as a crucial foundation for supporting the development of sustainable tourism destinations. They not only create enjoyable and memorable tourism experiences for visitors but also encourage the active participation of local communities in maintaining environmental quality and social values. If consistently implemented, these principles will be a key force in enhancing the competitiveness and positive image of tourist destinations in the eyes of tourists.